POPPIE: protocol for a randomised controlled pilot trial of continuity of midwifery care for women at increased risk of preterm birth - C. Fernandez Turienzo; D. Bick; M. Bollard; L. Brigante; A. Briley; K. Coxon; P. Cross; A. Healey; M. Mehta; A. Melaugh; J. Moulla; P. T. Seed; et al. (Trials, 2019)
Abstract Background High rates of preterm births remain a UK public health concern. Preterm birth is a major determinant of adverse infant and longer-term outcomes, including survival, quality of life, psychosocial effects on the family and health care costs. We aim to test whether a model of care combining continuity of midwife care with rapid referral to a specialist obstetric clinic throughout pregnancy, intrapartum and the postpartum period is feasible and improves experience and outcomes for women at increased risk of preterm birth. Methods This pilot, hybrid, type 2 randomised controlled implementation trial will recruit 350 pregnant women at increased risk of preterm birth to a midwifery continuity of care intervention or standard care. The intervention will be provided from recruitment (antenatal), labour, birth and the postnatal period, in hospital and community settings and in collaboration with specialist obstetric clinic care, when required. Standard care will be the current maternity care provision by NHS midwives and obstetricians at the study site. Participants will be followed up until 6–8 weeks postpartum. The composite primary outcome is the appropriate initiation of any specified interventions related to the prevention and/or management of preterm labour and birth. Secondary outcomes are related to: recruitment and attrition rates; implementation; acceptability to women, health care professionals and stakeholders; health in pregnancy and other complications; intrapartum outcomes; maternal and neonatal postnatal outcomes; psycho-social health; quality of care; women’s experiences and health economic analysis. The trial has 80% power to detect a 15% increase in the rate of appropriate interventions (40 to 55%). The analysis will be by ‘intention to treat’ analysis. Discussion Little is known about the underlying reasons why and how models of midwifery continuity of care are associated with fewer preterm births, better maternal and infant outcomes and more positive experiences; nor how these models of care can be implemented successfully in the health services. This will be the first study to provide direct evidence regarding the effectiveness, implementation and evaluation of a midwifery continuity of care model and rapid access to specialist obstetric services for women at increased risk of preterm birth. Trial registration ISRCTN37733900. Retrospectively registered on 21 August 2017.